The impact of transformational leadership, entrepreneurial behavior, and self-efficacy on performance: The mediating role of affective commitment - Rustam Munif; Sulha Sulha; Ahmad Yani T; Hendra Sulistiawan (STKIP Singkawang, 2025)
This study aims to develop performance through transformational leadership, entrepreneurial behavior, and self-efficacy through the mediating role of affective commitment at SMKs in West Kalimantan. The placement of affective commitment mediating variables that relate to transformational leadership, entrepreneurial behavior, and self-efficacy with performance. This study uses a quantitative approach with survey techniques. Data were collected through questionnaires and documentation from 254 teachers as a sample from a population of 3,999 teachers in 29 public and private vocational schools in eight districts / cities as data sources. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS version 7. The research findings show that transformational leadership, entrepreneurial behavior, and self-efficacy have a positive and significant effect on performance through the role of affective commitment, but transformational leadership and self-efficacy have a positive but insignificant effect on performance directly. The conclusion of this study provides a new contribution to the education management literature, especially in strengthening the role of affective commitment as a mediator, and provides practical implications for the development of leadership and vocational education policies in border areas. Recommendations for future research focus on transformational leadership and self-efficacy have a positive but insignificant effect on performance directly as a limitation of this research